The Development of an Integrated Strengthening Capacity Model for Students with Special Needs in Srisangwan School, Chiang Mai - Sriwilai, Phoungtong (Ph.D. in Social Sciences Journal, 2023)
This research article aimed to (1) study current state and future trends, the need to develop an integrated strengthening capacity model for students with special needs in Srisangwan School, Chiang Mai (2) to create an integrated strengthening capacity model for students with special needs in Srisangwan School, Chiang Mai and (3) to study the results of using the integrated strengthening capacity model for students with special needs, Srisangwan School, Chiang Mai. This research study uses the mixed methods research methodology. The research findings revealed that: (1) Current conditions of teachers, students, personnel, parents, and stakeholders Overall, at the level Moderate in all aspects. The need to develop an integrated capacity building model for students with special needs, Srisangwan School, Chiang Mai. Overall is at the highest level. (2) The result of creating the integrated strengthening capacity model for students with special needs in Srisangwan School, Chiang Mai, found that the development of an integrated strengthening capacity model for students with special needs in Srisangwan School, Chiang Mai has there components which are: SIEBN Model. For students with special needs, Srisangwan School, Chiang Mai. The results of the study of using of the development of an integrated strengthening capacity model for students with special needs in Srisangwan School, Chiang Mai found that Evaluation results for accuracy/suitability/feasibility/ benefits by experts the overall was at the high level. (3) The result of using the development of an integrated strengthening capacity model for students with special needs in Srisangwan School, Chiang Mai found that; academic year 2019 Students had the results of the integrated competency assessment an excellent level of 90.03 percent. and the satisfaction towards the results of using the integrated competency building model for learners with special needs at Srisangwan Chiang Mai School.